BUSINESS IMPACT OF EFFECTIVE TRAINING AND DEVELOPMENT PRACTICES OF BILLABLE RESOURCES IN PROFESSIONAL SERVICES ORGANISATIONS THAT BELONG TO SAAS COMPANIES - Bronet Campos, Jose Ramon (Digital Repository of Theses - SSBM Geneva, 2023)
Although retention of employees has been one of the most relevant topics in Human Resource Management, companies are still failing to address or even understand it effectively. Over the past years, numerous research pointed out to Training and Development (“T&D”) policies as a mechanism for maximising motivation and retention. Specific research domain deals with the importance of this in Professional Services (“PS”) in the Information Technology (“IT”) sector. However, the ability to set in place T&D practices that are meaningful to the business is not yet well known. There is also little known around what effective T&D looks like in these organisations. The purpose of this research is understanding if T&D practices can be effective while at the same time respectful with their business targets, this work studied Professional Services in a major business unit of a worldwide leader networking multinational company that is part of NASDAQ 100 and Fortune 100; compromising hundreds of employees, multiple regions and different T&D approaches across four fiscal years of data on where dramatic exceptional events, such as a Global Pandemic (COVID19) and BREXIT, occurred. Two statistical methods have been used with the intention of identifying healthy or unhealthy business Key Performance Indicators (“KPIs”): Mean analysis has been used to understand how business KPIs averages have deviated from their business targets; Variance has been used to understand the predictability of the same business KPIs by looking at the dispersion of datapoints. The results obtained by using Design Science Research (“DSR”) and the mentioned statistical methods produced two things: The first one is an innovative markerbased model presented in this research that organisations can use to develop effective T&D policies; the second one is that effective T&D in SaaS PS organisations can exist without having to sacrifice business targets. The impact on organisations that use the proposed marker-based model has the potential of not only improving retention, but also producing a higher quality of work, which ultimately enables companies to generate more revenue.